Looking beyond the Text : New Approaches to Scribal Culture and Practices in Ancient Egypt - Geoga, Margaret,; Motte, Aurore, (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2025., 2025)
Looking beyond the Text investigates the production, transmission, and reception of texts and manuscripts in ancient Egypt, focusing on the complex practices and culture of the scribes who made them. Drawing on theories and methods from other disciplines such as literary studies, neuroscience, and book history, the authors discuss the physical practices of writing, social contexts of texts and manuscripts, and scribes themselves. The papers examine a wide range of manuscripts, including letters, medical compendia, poems, religious corpora, and other text genres, written on varied media in different time periods. The resulting collection offers new perspectives on the key role of scribes in ancient Egypt and models more contextualized and materially informed modes of philology.